KARAKTERISASI KROMOSOM SEL HETEROHIBRIDA DENGAN TEKNIK KARYOTIPING - Berata, I Ketut (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
The aim of the research was to characterize the chromosomal structure of the heterohybride cells by karyotyping technique. Heterohybride cells were made by fusion of Bali cattle lymphocyte cells with mouse myelomma in selective medium which contains hypoxanthin, aminopterin and thymidine. Those cells which showed growth then were identified, selected and isolated for characterizing its chromosomal structure by karyotyping technique. The result showed that all of the chromosomal structure of the heterohybride cells were diploidy. The average of diploidy chromosome of heterohybride cells were 97 diploid Bali cattle lymphocyte cells and myelomma of mouse. The conclusion of the research is the heterohybride cells do not contain abnormal chromosome and are most potent to develop as candidate of Jembrana diseases vaccine.